49 Histomorphic Analysis of the Effect of Day and Level of Colostrum Intake on Jejunum Development. (7th May 2021) - Sheets, Jocelyn; Suarez-Trujillo, Aridany; Teeple, Kelsey; Senn, L Kirsten; Stewart, Kara R; Casey, Theresa
Abstract: The first milk sows synthesize is colostrum, and is only available to the neonate right after birth. Colostrum provides immunity, nutrients, energy, and bioactive factors which are essential for the survival, growth, and development of newborn piglets. The first few days after birth the gastrointestinal (GI) tract undergoes developmental changes and rapid growth in response to bioactive factors in milk. We hypothesized that amount of colostrum a neonate consumes the first 24 h postnatal effects the development of the GI tract. The objectives of this study were to measure the histomorphic growth of the jejunum between birth (day 0, D0) and postnatal day 7 (D7) and to determine the effect of ingesting a high versus low amount of colostrum. Gilts were identified at birth and immediately euthanized (D0, n = 6) or bottle fed a 24 h colostrum dose of 10% (COL10, n = 7) or 20% (COL20, n = 7) of birth body weight. Colostrum fed neonates were returned to birth sows after 24 h and allowed to nurse naturally until postnatal (D7), when gilts were euthanized. Gilts were dissected and jejunum was removed, weighed and placed in buffered formalin for preparation of histological sections. Five µm sections were mounted on glass slides and stained with hematoxylin and eosin (H&E). Images were captured using light microscopy at 10X magnification. ImageJ was used to measure villi length, width, stromal area, epithelial area, and crypt length. T-test analysis indicated that there was no difference between COL10 and COL20 in any of the morphological features (P > 0.05), however between D0 and D7 villi width, epithelial area, and crypt length increased (P < 0.05). Differences in histomorphology across the first week postnatal was not affected by level of colostrum intake in the first 24 h postnatal.